Fenomena Dakwah Digital di Media Sosial dalam Perspektif Mahasiswa Muslim Gen Z dan Pengaruhnya terhadap Akhlak Mereka - Lisa Yulianti; Aceng Kosasih; Mokh. Iman Firmansyah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to explore how Gen-Z Muslim students interpret, respond to, and assess digital da'wah they consume on social media and how it affects their morals in everyday life. This study uses a quantitative approach with a non-experimental design through a correlational survey method with Digital Da'wah on Social Media as the Independent variable and the Morals of Gen-Z Muslim Students as the dependent variable. The results show that the majority of respondents agree and strongly agree with all items in the digital da'wah variable, which illustrates that digital da'wah is considered relevant, interesting, easily accessible, and has a strong da'wah essence. In the morals variable, respondents also predominantly show the agree and strongly agree categories, which indicates that the morals of Gen Z Muslim students are in the good category. The results of the correlation test obtained a coefficient value of 0.652 which is included in the strong and positive relationship category, so it can be concluded that digital da'wah on social media has a strong relationship and a positive influence on the morals of Gen Z Muslim students